PENGARUH DOSIS ALKALINITAS TERHADAP KINERJA PERTUMBUHAN UDANG WINDU (Penaeus monodon) YANG DI PELIHARA PADA SUHU 33 0 C - Mustafa Kamal; Suri Purnama Febri; Teuku Fadlon Haser; Muhammad Safir; Ahyar Pulungan; Devita Aritya Sri Widya; Sari Afriani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Tiger prawns are a marine commodity that has high economic value in Indonesia and abroad. This research aims to determine the right time for administering dolomite lime solution to increase tiger prawn growth. This research used an experimental method with 4 treatments and 3 repetitions. The treatments tested were P1 (giving a dolomite lime solution on day 0 before stocking), P2 (giving a dolomite lime solution on the 15 day after stocking), P3 (giving a dolomite lime solution on the 30th day after stocking), and P4 (giving dolomite lime solution on the 30 day after stocking). administration of dolomite lime solution on the 45 day after stocking). The results of the research showed that administration of dolomite lime solution had an effect on absolute length growth, absolute weight growth and daily growth rate. Meanwhile, survival and feed conversion ratios did not have significant differences, neither did water quality. In general, water quality is not affected by the treatment given. The highest absolute length growth was produced at P3 at 4.1 cm. The highest absolute weight growth was obtained in treatment P3 with a result of 1.28 g, while the lowest absolute weight growth was obtained in treatment P4 at 1.13 g. The highest daily growth rate was produced in treatment P3, namely 6.14%, while the lowest daily growth rate was produced in P2, namely 5.28%.